Marijuana consumption among professional tennis players - Maquirriain, J.; Baglione, R. (Medicine and Science in Tennis, 2009)
Author discusses the mariuhana abuse among profi tennis players as well as the clinical implications of cannabis consumption. Summary: Cannabis consumption produces severe harm effects to athletes` health and its abuse by adolescent and young adults should not be underestimated or considered as a normal recreational behavior. An ongoing discussion exists regarding drug education and testing in the sport community. Sports physicians should play a variety of relevant roles serving as doctors and also as educators and counselors of young tennis players regarding the deleterious effects of marijuana abuse. Likewise, the earliest intervention usually leads to the most optimal treatment response.